2018
DOI: 10.1103/physreva.98.032302
|View full text |Cite
|
Sign up to set email alerts
|

Imbalance entanglement: Symmetry decomposition of negativity

Abstract: In the presence of symmetry, entanglement measures of quantum many-body states can be decomposed into contributions arising from distinct symmetry sectors. Here we investigate the decomposability of negativity, a measure of entanglement between two parts of a generally open system in a mixed state. While the entanglement entropy of a subsystem within a closed system can be resolved according to its total preserved charge, we find that negativity of two subsystems may be decomposed into contributions associated… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
156
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 121 publications
(159 citation statements)
references
References 51 publications
3
156
0
Order By: Relevance
“…Note that some works normalize each block by each trace [21,22,23] before calculating the entropies, which thus quantify the entanglement after a projective charge measurement. We prefer not to do so and instead use (6), following [19,20], because the resulting entropies are not only more accessible to calculations, but are also directly experimentally measurable, using either the replica trick [20,24,25], or random time evolution which conserves the charge [26,27]. Let us also note that S 1 (Q A ) is simply the distribution P (Q A ) of charge in subsystem A. WhenQ can assume any integer value (e.g., when particle number or total S z are conserved), we define the flux-resolved REE as S n (α) = Tr ρ n A e iαQ A .…”
Section: Introductionmentioning
confidence: 99%
“…Note that some works normalize each block by each trace [21,22,23] before calculating the entropies, which thus quantify the entanglement after a projective charge measurement. We prefer not to do so and instead use (6), following [19,20], because the resulting entropies are not only more accessible to calculations, but are also directly experimentally measurable, using either the replica trick [20,24,25], or random time evolution which conserves the charge [26,27]. Let us also note that S 1 (Q A ) is simply the distribution P (Q A ) of charge in subsystem A. WhenQ can assume any integer value (e.g., when particle number or total S z are conserved), we define the flux-resolved REE as S n (α) = Tr ρ n A e iαQ A .…”
Section: Introductionmentioning
confidence: 99%
“…We obtain the flux resolved RNs by adding vertex operators at the boundaries between the subsystems 43 . The additivity of the scaling dimensions, Eq.…”
Section: B the Entanglement Negativitymentioning
confidence: 99%
“…The numerical method for the exactly solvable XX model is developed in Ref. 43 and based on the fact that the partially transposed RDM is a sum of two Gaussian matrices 81,82 :…”
Section: B Entanglement Negativitymentioning
confidence: 99%
See 1 more Smart Citation
“…For any given state, clearly E = log(2N + 1). The (logarithmic) negativity has been studied in several contexts, ranging from harmonic chains and lattices [44][45][46][47][48][49][50][51][52][53] to quantum spin models [54][55][56][57][58][59][60][61][62][63][64][65] , from conformal and integrable field theories [66][67][68][69][70][71][72][73][74][75] to non-equilibrium situations [75][76][77][78][79][80][81] and intrinsic and symmetry-protected topological orders [82][83][84][85][86][87][88][89][90] . For fermionic models, it has been shown that the partial timereversal transpose is a more appropriate object to characterise t...…”
Section: Introductionmentioning
confidence: 99%